Descompactação e correção da acidez do solo subsuperficial em sistema plantio direto - Kraemer, Luciano Borges (2022)
The No-Tillage System has brought numberless benefits to agriculture, increasing the level of crop productivity as from its implementation. However, throughout the years, the loss of some of the concepts applied in the practice of soil management system, and the increase in the traffic of heavier and heavier machinery in the field, have caused a subsurface soil compaction, especially in clayey soils. Furthermore, due to the non-revolving of the soil, the efficiency of the application of chemical soil amendments was limited to the superficial layers. The aim of this study was to evaluate the efficiency of the soil decompresser and fertilizer Fertillus 700 in the chemical and physical improvement of the soil in the subsurface of a Red Latosol and its effects in the deep rooting in the no-tillage system. The survey was carried out in the Experimental Area of the Federal University of Paraná (UTFPR), Dois Vizinhos Campus. The demarcation used was one of randomized blocks of 5.6 m x 20 m which received 5 treatments and 4 repetitions each, the entire area was managed under cosolidated no-tillage system and the green cover of Black Oats (Avena strigosa). Soybeans-beans-black oat-soybeans were planted in sequence. The treatments consisted of T0: witness, T1: only subsoiling, T2: Amendment Subsoiling in 30 to 40-cm profile with Ca(OH)²,T3: Ca(OH)² Amendment Application on surface, T4: Ca(OH)² Amendment Subsoiling in 0,15 to 0,30 m profile. The product used was Calcium Hydroxide (7000i – 70% CaO) in the form of a 135%-PRNT dry fine powder. The dosage used was 1 mg ha⁻¹ for the surface and subsurface treatments. Along the profile of the furrow stems, the different layers of 0,00-0,05 m; 0,05-0,10 m; 0,10-0,20 m; 0,20-0,30 m and 0,30-0,40 m.were evaluated as well as the physical attributes (RP, density, macroporosity. microporosity, total porosity), and the chemical attributes (ph, MO, V%, H+Al, Al⁺³, m%, Ca⁺², Mg⁺², P, K⁺). After 12 months of mechanical intervention in the subsoiling treatments, the RP readings were below 2 MPa, and this criterion was not a limiting factor for the development of the crops used in the management system. Although there was an improvement in the physical conditions of the soil in relation to Ma, Mi, PT and Ds of the soil, 14 months after the mechanical intervention, these variables did not significantly reflect for MS of black oat, bean yield, and soybean crop second year between the treatments. Soybean productivity in the first year of evaluation showed significance in the treatment in which there was corrective subsoiling at a depth of 0.15 to 0.30 m from the soil in relation to the control.